Discordance predictor between fractional flow reserve and resting full-cycle ratio in clinical characteristics. (25th November 2020) - Ohashi, H; Takashima, H; Ando, H; Suzuki, A; Sakurai, S; Nakano, Y; Sawada, H; Fujimoto, M; Suzuki, W; Waseda, K; Amano, T
Abstract: Introduction: Fractional flow reserve (FFR) is a gold standard method to evaluate functional lesion severity in daily clinical practice. Recently, the resting full-cycle ratio (RFR) which was newly developed resting indices was launched. Unlike other resting indices evaluated in diastolic phase, RFR is evaluated during entire cardiac phase. Previous studies showed discordance predictors between FFR and instantaneous wave-free ratio. However, it is previously unreported what predictor cause discordant outcome between FFR and RFR. Purpose: The purpose of this study was to evaluate clinical predictors of discordance between FFR and RFR. Methods: A total of 156 patients with 220 lesions were prospectively enrolled in this study. RFR was evaluated before inducing hyperemia. FFR was measured after intravenous adenosine triphosphate administration (180 mcg/kg/min). According to FFR and RFR values, the patients and lesions were classified into 4 groups: Concordant negative (Group-1 [n=114]: FFR >0.80, RFR >0.89); negative FFR and positive RFR (Group-2 [n=18]: FFR >0.80, RFR ≤0.89); positive FFR and negative RFR (Group-3 [n=25]: FFR ≤0.80, RFR >0.89); Concordant positive (Group-4 [n=63]: FFR ≤0.80, RFR ≤0.89). Among them, discordance predictors with clinical characteristics between RFR and FFR were compared using by two separate logistic regression analyses. (Group-1 vs. Group-2, Group-3 vs. Group-4, respectively). Age, sex and those predictors with a p value ≤0.10 were included in a multivariate regression analysis using by forward stepwise selection to identify independent predictors of discordance. Results: On multiple regression analysis, hemodialysis (HD) (OR:6.072 [1.090–33.836]), peripheral artery disease (PAD) (OR:9.053 [1.776–46.162]) and left anterior descending artery (LAD) (OR:9.264 [2.092–41.031]) were significantly associated with positive RFR among negative FFR groups (Groupe 2 discordance). Conversely, diabetes mellitus (DM) (OR:0.212 [0.062–0.721]) and Hb (OR:1.480 [1.102–1.987]) were significantly associated with negative RFR among positive FFR groups (Groupe 3 discordance) Conclusions: Since the clinical characteristics with HD, PAD, LAD, DM and Hb may influence concordant with FFR during RFR evaluation, it should be considered when interpreting RFR. Funding Acknowledgement: Type of funding source: None